1998
DOI: 10.1063/1.366825
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic picture of the effects of rubbing on polyimide surfaces and liquid crystal pretilt angles

Abstract: A mechanistic picture of the effects of rubbing on polyimide alignment layer (AL) surfaces and nematic liquid crystal (LC) pretilt angles (ΘP), leading to establishing a mechanism of determination of ΘP’s, was proposed on the basis of the study of the change in surface polarity of a polyimide AL with the rubbing force and density, and the subsequent changes in the ΘP and the azimuthal anchoring energy. In the regime of relatively weak rubbing where inhomogeneous, patchy surface modification (the microscopic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 39 publications
5
67
0
Order By: Relevance
“…The errors in determining these variables through fitting are calculated by estimating the deviation when the cell thickness was varied by 10% with respect to the cell gap created by the spacers (50μm). The fitted parameters are in good agreement with literature values for pretilt 28 (typically between 1° and 2.1° for various LC systems) and the value of splay elastic constant for E7 (11.7 pN) as specified in Merck data sheet. The fitted values for the pretilt and the splay elastic constant are used in the simulations to determine the spatial distribution of alignment of the LC in the cells.…”
Section: Pretilt and Elastic Constantssupporting
confidence: 72%
“…The errors in determining these variables through fitting are calculated by estimating the deviation when the cell thickness was varied by 10% with respect to the cell gap created by the spacers (50μm). The fitted parameters are in good agreement with literature values for pretilt 28 (typically between 1° and 2.1° for various LC systems) and the value of splay elastic constant for E7 (11.7 pN) as specified in Merck data sheet. The fitted values for the pretilt and the splay elastic constant are used in the simulations to determine the spatial distribution of alignment of the LC in the cells.…”
Section: Pretilt and Elastic Constantssupporting
confidence: 72%
“…Here, we present a pressure-driven or Poiseuille flow study, examining the properties of liquid crystal cells filled with 5CB (4-Cyano-4 0 -pentylbiphenyl) having high (almost normal to the flow) initial azimuthal alignment angle ( 0 ) and small surface pretilt ( 0 ) (from buffed polyimide [11]) in both the splayed and parallel aligned states (see Fig. 1).…”
mentioning
confidence: 99%
“…10 for POSS-doped PI and UV-treated PI alignment layers, respectively. The influence of surface energy of PI alignment layers on pretilt angles had been investigated (Paek et al, 1998;Yu et al, 1999;Ban & Kim, 1999). It showed that an alignment layer with higher surface energy gives the lower pretilt angle due to the increased attractive strength between LC molecules and molecules of the alignment layers.…”
Section: Characteristics Of Pismentioning
confidence: 99%
“…The pretilt angle is very important and required for LC devices to obtain a defect-free alignment and also to improve their electro-optical performance, such as driving voltage, response time, color performance and viewing angle. However, the applications of conventional PIs in LCDs are limited by a small tuning range of pretilt angle (~ few degrees) either by controlling the rubbing depth or the number of rubbings (Paek et al, 1998). The pretilt angle of an LCD is either near zero degrees or 90 degrees for using the conventional homogeneous and homeotropic PI materials, respectively.…”
Section: Introductionmentioning
confidence: 99%